SPOT WELDING RESIDUAL STRESSES ASSESSMENT USING NONLINEAR NUMERICAL TECHNIQUE (Journal of Engineering, 2008)
A description is given of the resistance spot welding process in terms of internal behavior of the weld as welding takes place. Heat input due to spot welding of steel sheet plate causes temperature gradient in the parent metal. After cooling, residual stresses appear around the welding zone reducing the strength. Residual stresses are a result of the temperature gradient and the dependency of material properties on the temperature, such as yield strength, elasticity modulus, and thermal expansion coefficient. Nonlinear transient heat transfer analysis performed in order to obtain the temperature distribution in the welded part .A nonlinear thermo–plastic stress analysis is then performed to predict the stress and strain fields during and after welding. The material properties such as yield strength, elasticity modulus, convection coefficient, conduction, specific heat, and thermal expansion coefficient are used as a function of temperature. The heat transfer results are compared with experimental results performed within the scope of work of this study. On the other hand, the residual stress results are compared with experimental result obtained from literature .The comparison shows good agreement between numerical and experimental results.